2009
DOI: 10.1017/s0025315409003105
|View full text |Cite
|
Sign up to set email alerts
|

Trophic structure of soft-bottom macrobenthos in an inlet in north-western Spain

Abstract: The trophic composition of macrobenthic communities in intertidal and subtidal soft-bottoms of the Ensenada de San Simón (north-western Spain) was found to be related to a number of environmental variables. Distribution and abundance of trophic groups have been studied, to provide essential baseline information for monitoring the area, after its designation as a Natura 2000 Special Conservation Zone. Analyses of trophic data showed a numerical predominance of the herbivores in the inner part of the inlet, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…Median grain size (MGS) for the FL station was 12.3 ±1.8 µm, indicating this sample site lies in the range of muddy sediments. Previous studies in the Ría de Vigo (Cacabelos et al, 2009;Rodil et al, 2009) showed that sediments with similar MGS (10 -13 µm) were dominated by surface and subsurface deposit feeders. Deposit feeders obtain their nutritional intake mainly from sedimented organic matter (Heip et al 1995) and would mainly favour aerobic processes and oxidized sediment conditions as they enhance oxygen transfer to the sediment burrow irrigation (Welsh 2003).…”
Section: Benthic Oxygen Fluxesmentioning
confidence: 93%
“…Median grain size (MGS) for the FL station was 12.3 ±1.8 µm, indicating this sample site lies in the range of muddy sediments. Previous studies in the Ría de Vigo (Cacabelos et al, 2009;Rodil et al, 2009) showed that sediments with similar MGS (10 -13 µm) were dominated by surface and subsurface deposit feeders. Deposit feeders obtain their nutritional intake mainly from sedimented organic matter (Heip et al 1995) and would mainly favour aerobic processes and oxidized sediment conditions as they enhance oxygen transfer to the sediment burrow irrigation (Welsh 2003).…”
Section: Benthic Oxygen Fluxesmentioning
confidence: 93%
“…Most studies of macrobenthic trophic structure tend to classify benthic fauna in terms of strictly defined trophic groups only (e.g. Chardy & Clavier 1988, Gaston & Nasci 1988, Ricciardi & Bourget 1999, García-Arberas & Rallo 2002, Coyle et al 2007, Albano & Obenat 2009, Cacabelos et al 2009, Dolbeth et al 2009). Most commonly these trophic groups are: suspension feeders, deposit feeders (surface and subsurface), carnivores, herbivores and omnivores.…”
mentioning
confidence: 99%
“…Email: tristanjstringer@gmail.com physical factors such as salinity, tidal exposure, sediment size and oxygen concentration (Findlay 1981;Brito et al 2009). On a habitat scale (cm 2 Ám 2 ) biological variables increase in importance (Findlay 1981;Sandulli & Pinckney 1999;Azovsky et al 2004), although these biological factors are often themselves shaped by physical factors (Hogue & Miller 1981;Hicks & Coull 1983;De Troch et al 2006;Cacabelos et al 2009). The factor which has been suggested to have the most influence on species distribution is sediment size (Findlay 1981;Hicks & Coull 1983;Azovsky et al 2004); in particular the proportion of the silty (B63 mm) sediment fraction (Hicks & Coull 1983;Udalov et al 2005;Cacabelos et al 2009).…”
Section: Introductionmentioning
confidence: 99%